PPFIA4 Promotes Colon Cancer Cell Proliferation and Migration by Enhancing Tumor Glycolysis - Huang, Jia; Yang, Meiling; Liu, Zhaoxia; Li, Xiaoqian; Wang, Junfeng; Fu, Nian; Cao, Ting; Yang, Xuefeng (Frontiers in Oncology, 2021)
Dysregulated glycolysis is one of the mechanisms employed by cancer cells to facilitate growth and metastasis. Here we aimed to characterize the PPFIA4 gene, as a glycolysis-related oncogene in promoting the proliferation and migration of colon cancer cells. Using bioinformatical tools including The Cancer Genome Atlas (TCGA) and Gene Expression Profiling Interactive Analysis (GEPIA), we found that PPFIA4 expression and methylation levels were higher in colon cancer tissues of different stages than in normal tissues. Higher PPFIA4 level was also positively correlated with poorer survival of patients. PPFIA4 upregulation also correlated with poor prognosis and higher clinical stages of colon cancer patients. Colon cancer cell viability, migration and migration were enhanced after PPFIA4 overexpression. EMT markers and glycolysis were upregulated after PPFIA4 overexpression. PPFIA4 expression was found to be positively correlated with PFKFB3 and ENO2 levels, while knockdown of PFKFB3 and ENO2 reduced cell proliferation, migration, invasion and glycolysis. PPFIA4 upregulation is a potential biomarker in colon cancer which promotes proliferation, migration, invasion and glycolysis. The upregulation of PFKFB3/ENO2 signaling by PPFIA4 is a potential mechanism underlying the oncogenic effects of PPFIA4.